Lepidium peruvianum ingestion and the development of the of young rats holtzman - Campodánico Reátegui, Carlos (2009)
Lepidium peruviam (Maca), is a tuber with excellent nutritional and medicinal qualities due to its mineral and chemical compounds: vitamins, proteins, fatty acids, carbohydrates, tannins, and alkaloids. Method. This experimenta1 study aimed to determine the effect of Maca in the development of sex cells in mammals. The study conducted in 20 young Holtzman rats divided into two samples, in the experimental one rats consumed two grams of Maca daily for 30 days. Animals were sacrificed and then they were dissected; samples were histological studied. Results and conclusions. We noted that the use of Maca was very effective in the development of Sertoli and Leydig cells, and quite effective in spermatocytes development.